Cerebral Gnathostomiasis: An Unusual Course of Recurrent Hemorrhagic Stroke - Wanakorn Rattanawong; Pasin Hemachudha; Prakit Anukoolwittaya; Thanakit Pongpitakmetha (Annals of Neurology, 2022)
A 32-year-old Thai woman, who was previously healthy, was referred from a provincial hospital due to multiple recurrent episodes of hemorrhagic stroke within 3 months. In her first episode, she complained of severe thunderclap headache. Computer tomography (CT) of the brain revealed a subarachnoid hemorrhage in her left high frontal region. One month later, she had a sudden spastic dysarthria. Another CT was done showing a subarachnoid hemorrhage in her left parietal lobe and an ill-defined hypodensity lesion in her left posterior limb of the internal capsule. Plan for her referral was initiated but she later developed a new right hemiparesis and seizure within 2 weeks. A repeated CT showed intraparenchymal hemorrhage in the left temporal lobe. Therefore, she was referred to our facility. On examination, she was able to follow commands. Spastic dysarthria was prominent with right hemiparesis (Medical Research Council grade IV) and right facial weakness (upper motor neuron type). She had hyperreflexia on her right, both upper and lower limbs. Brain magnetic resonance imaging (MRI) showed T2-fluid-attenuated inversion recovery (FLAIR) imaging of a 4 cm hypersignal intensity lesion in the left basal ganglion and left insular lobe with vasogenic edema (Figure 1A). In a T1 with gadolinium sequence of the same region, it showed left leptomeningeal and gyral enhancement along the left cerebral cortex (Figure 1B). Susceptibility weighted imaging of the corona-radiata showed an abnormal hemosiderin line crossing the corpus callosum from the right lateral ventricle to the left lateral ventricle (Figure 1C), which is located beyond the normal vascular structure. In a coronal T2* gradient echo imaging, it showed an abnormal hemosiderin line crossing from the left basal ganglion down into left midbrain and penetrating into the right midbrain (Figure 1D). The hemosiderin line is suspected to be the migration track of the larvae. MRI scans of the arteries was unremarkable. Because the clinical manifestation of the patient did not give enough clues to differentiate the diagnosis, a thorough consideration of the neuroimaging should be elaborated to look for further clues, including specific locations and signs. Regarding the imaging findings, a unique pattern of hemorrhagic track-like appearance crossing the 2 hemispheres could narrow down the differential diagnosis. Intravascular lymphoma and primary central nervous system vasculitis were in the differential diagnosis because they could represent in multiple hemorrhage with hemosiderin stain in the corpus callosum. However, due to the hemorrhagic track-like appearance that was beyond the vascular structure, a larvae migration should be considered. Although, both Angiostrongylus cantonensis and Gnathostoma Spinigerum could cause hemorrhagic tracks, but the long hemorrhagic track-appearance with intracerebral hemorrhage and subarachnoid hemorrhage are more pathognomonic to Gnathostoma Spinigerum. Laboratory testing shows hemoglobin of 11 g/dL, and total leukocyte count of 7,310/uL in which eosinophil count was found to be 1,100/uL (15%). Lumbar puncture revealed 110 white blood cells, of which 82% were polymorphonuclear cells and 18% were mononuclear cells; protein levels were 80 mg/dL, sugar levels were 34 mg/dL (blood glucose was 242 mg/dL), and red blood cells were also found to be 5,120 cells. Serum 24-kDa anti-Gnathostoma Spinigerum IgG by immunoblot test was positive. Therefore, the patient was diagnosed with cerebral gnathostomiasis. The patient was treated with 200 mg of albendazole 2 tablets daily for 3 weeks with oral prednisolone (1 mg/kg). She remained stable without recurrent hemorrhagic stroke. Gnathostoma Spinigerum are zoonotic helminth found exclusively in tropical areas. Humans are believed to be accidental hosts in which they are infected by eating raw freshwater fish and shellfish. Ingestions of snakes, frogs, and wild ducks have also been reported.1 The larvae stage of the helminth is responsible for the clinical manifestation in humans. The head bulb contains 4 hooklet rows which are responsible for the penetration of the body tissues (Figure 2). Five main clinical presentations that have been described in the literature for neurognathostomiasis includes radiculopathy, myelopathy, intracerebral hemorrhage, subarachnoid hemorrhage, and mixed (radiculomyelitis and radiculomyeloencephalitis).2 In addition, certain clinical clues, including intermittent migratory swelling and creeping eruption, may help in the diagnosis. MRI showing migration of larvae are pathognomonic signs for neurognathostomiasis.3 Because gnathostomiasis is a rare disease even in tropical countries, a thorough attention to neuroimaging could narrow down the diagnosis and prompt further investigations. Testing for serum antibody of Gnathostoma spp. is helpful, but not routinely investigated. Therefore, a high suspicion of this condition could elicit the correct diagnosis. Treatment with albendazole or ivermectin plus corticosteroid is recommended.4 However, no randomized control trial has been established. The diagnosis is challenging and needs a high degree of suspicion. The authors thank Dr. Padet Siriyasatien, Dr. Kobpat Phadungsaksawasdi, and their team from the Department of Parasitology, Faculty of Medicine, Chulalongkorn University, for providing the larvae image (Figure 2). W.R., T.P., and P.H. contributed to the conception and design of the study. W.R., T.P., P.A., and P.H. contributed to the acquisition and analysis of data. W.R., T.P., P.A., and P.H. contributed to drafting the text or preparing the figures. The authors report no conflict of interest.
Keywords: Parasites and Host Interactions; Mollusks and Parasites Studies; Parasitic infections in humans and animals